2013
DOI: 10.1111/ocr.12016
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of volumetric measurement of simulated root resorption lacunas based on cone beam computed tomography

Abstract: The accuracy of 3-D quantitative volumetric measurement of simulated root resorption based on CBCT was fairly good in detecting simulated resorption cavities larger than 3.47 mm(3), while it was not sufficient for measuring resorption cavities smaller than 1.07 mm(3) . This method could be applied in future studies of root resorption although further studies are required to improve its accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 21 publications
0
25
0
2
Order By: Relevance
“…A recent case report using CBCT, microfocus CT and scanning electron microscopy describes the valuable use of CBCT in the diagnosis of root resorption[27]. Furthermore, ex-vivo studies using bovine teeth showed that, when compared to measurements made from micro CT, CBCT scans detect simulated defects of 0.6 mm depth accurately[28]. …”
Section: Introductionmentioning
confidence: 99%
“…A recent case report using CBCT, microfocus CT and scanning electron microscopy describes the valuable use of CBCT in the diagnosis of root resorption[27]. Furthermore, ex-vivo studies using bovine teeth showed that, when compared to measurements made from micro CT, CBCT scans detect simulated defects of 0.6 mm depth accurately[28]. …”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that the results of this study were obtained from images having a voxel resolution of 200 mm. Wang et al 34 evaluated the accuracy of volumetric measurement of simulated root resorption cavities with CBCT using a 125-mm voxel size and concluded that CBCT was not sufficient for detecting cavities smaller than 1.07 mm 3 because of manual segmentation. Thus, in our study, small volumetric changes might not be discerned, causing an underestimation of volumetric changes.…”
Section: Limitationsmentioning
confidence: 99%
“…The accuracy of CBCT imaging in measuring osteolytic lesion volume was assessed in several studies (6)(7)(8)(9). Ahlowalia et al (7) compared the accuracy of CBCT imaging with micro-computed tomographic imaging in measuring irregularshaped cavities created in bovine bone.…”
mentioning
confidence: 99%